2020
DOI: 10.26434/chemrxiv.13311614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substrate Inhibition by the Blockage of Product Release and Its Control by Tunnel Engineering

Abstract: <div> <p>Substrate inhibition is the most common deviation from Michaelis-Menten kinetics, occurring in approximately 25% of known enzymes. It is generally attributed to the formation of an unproductive enzyme-substrate complex after the simultaneous binding of two or more substrate molecules to the active site. Here, we show that a single point mutation (L177W) in the haloalkane dehalogenase LinB causes strong substrate inhibition. Surprisingly, a global kinetic analysis suggested that this inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Substrate inhibition is the most common deviation from Michaelis-Menten kinetics, occurring in about 25% of known enzymes. It is generally attributed to the formation of an unproductive enzyme-substrate complex after the simultaneous binding of two or more substrate molecules to the active site [37]. Thus, our model behaves much as in the case of a substrate inhibition mechanism, with one important exception: in our case, we have two enzyme monomers bound to one substrate molecule, whereas the substrate inhibition model considers the ES 2 system, i .…”
Section: Discussionmentioning
confidence: 99%
“…Substrate inhibition is the most common deviation from Michaelis-Menten kinetics, occurring in about 25% of known enzymes. It is generally attributed to the formation of an unproductive enzyme-substrate complex after the simultaneous binding of two or more substrate molecules to the active site [37]. Thus, our model behaves much as in the case of a substrate inhibition mechanism, with one important exception: in our case, we have two enzyme monomers bound to one substrate molecule, whereas the substrate inhibition model considers the ES 2 system, i .…”
Section: Discussionmentioning
confidence: 99%
“…40 Considering that both sites in PchP are found in a common cavity, where the entrance to the AS implies a first access to the IS, the mechanism could be of the blockage type for the entry of substrates or for the release of products, such as the one recently proposed for the haloalkane dehalogenase of Sphingobium japonicum UT26. 41 However, despite still not knowing the biological meaning of PchP inhibition, it seems clear that because it is a differential and distinctive aspect with respect to PHOSPHO1 it can be considered for pharmacological purposes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Previous studies indicated that the characteristics of substrate access tunnels can have a decisive influence on enzyme-substrate specificity and activity [53][54][55][56]. In t-PlaF, we focused on T1 and T2 because only these two allow direct access of GPL or LGPL substrates from the membrane in the t-PlaF A configuration.…”
Section: Discussionmentioning
confidence: 99%